New or little known species of Tortricidae for the Italian fauna (Bollettino di zoologia agraria e bachicoltura, 2024)
The presence of seven species of Lepidoptera Tortricidae new for Italian fauna is reported: Cochylis flaviciliana (Westw.), Phtheochroa pulvillana (H.-S.), Tosirips magyarus Raz., Gypsonoma imparana M-R., Cydia andabatana (Wolff), Cydia ulicetana (Haw.) and Dichrorampha forsteri Obr.. Additional data around twenty poorly known species are also given.
Keywords: Tortricidae; Italian fauna; new records